The latest research progress on the clinical application of nemonoxacin - Yin, Hui; Shao, Yingchun; Sun, Fusheng (Frontiers in Medicine, 2025)
Nemonoxacin is a novel non-fluorinated quinolone antibacterial agent, characterized by a broad antibacterial spectrum, strong antibacterial activity, low protein binding rate, high oral bioavailability, and extensive tissue distribution. Its unique pharmacological properties confer high clinical application value. In the context of bacterial resistance, this article aims to provide a comprehensive review of nemonoxacin’s antibacterial activity, immunomodulatory effects, and its application in infectious diseases as well as in patients with hepatic or renal insufficiency, with the goal of offering more drug options for clinical treatment and providing a reference for future clinical research and widespread application.